2015
DOI: 10.1111/gcbb.12272
|View full text |Cite
|
Sign up to set email alerts
|

Crassulacean acid metabolism (CAM) offers sustainable bioenergy production and resilience to climate change

Abstract: Biomass production on low-grade land is needed to meet future energy demands and minimize resource conflicts. This, however, requires improvements in plant water-use efficiency (WUE) that are beyond conventional C3 and C4 dedicated bioenergy crops. Here we present the first global-scale geographic information system (GIS)-based productivity model of two highly water-efficient crassulacean acid metabolism (CAM) candidates: Agave tequilana and Opuntia ficus-indica. Features of these plants that translate to WUE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 63 publications
1
40
1
2
Order By: Relevance
“…This study is the first field experiment to compare Agave production under a range of controlled water inputs. The production of Agave species measured in this study was lower than previously reported Agave biomass in semiarid regions ( e.g., Davis et al ., ), but A. tequilana production was similar to modeled projections of A. tequilana biomass potential in the United States (Owen et al ., ). There are no previous reports of A. americana production, but yields were lower than theoretical production rates for CAM plants (Nobel, ; Borland et al ., ; Davis et al ., ), and far below the theoretical predictions of 43 Mg ha −1 yr −1 for high‐yielding CAM plants (Borland et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…This study is the first field experiment to compare Agave production under a range of controlled water inputs. The production of Agave species measured in this study was lower than previously reported Agave biomass in semiarid regions ( e.g., Davis et al ., ), but A. tequilana production was similar to modeled projections of A. tequilana biomass potential in the United States (Owen et al ., ). There are no previous reports of A. americana production, but yields were lower than theoretical production rates for CAM plants (Nobel, ; Borland et al ., ; Davis et al ., ), and far below the theoretical predictions of 43 Mg ha −1 yr −1 for high‐yielding CAM plants (Borland et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…; Butterbach‐bahl & Kiese ) and with productivity models (Owen & Griffiths ; Owen et al . ; Lewis et al . ), but canopy‐scale studies are rare.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, cuando se controla el efecto de los otros factores, solamente la cobertura de mantillo tiene una asociación fuerte con la cobertura de A. angustifolia. Es conocida la capacidad de los agaves de sobrevivir en suelos pobres y secos (Ramírez-Tobías et al, 2014;Owen et al, 2015), y su habilidad de asociarse con hongos micorrizó-genos (Carmona-Escalante et al, 2013), que le permiten aumentar su eficiencia en la adquisición de agua y nutrimentos edáficos.…”
Section: Discussionunclassified